ANALISIS PENGARUH KOMITMEN ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada PT. Madu Baru Bantul Yogyakarta) - Camela Ikey Badhoeg Dadie; Rini Nugraheni (JURNAL STUDI MANAJEMEN ORGANISASI, 2016)
This research is motivated by the presence of problems of the many employeeswho left the company at PT Madu Baru Bantul, Yogyakarta. Moreover, accordingto the pre-survey interviews that have been done, there is a lack of communicationbetween the leaders with employees. Objective of this study was to analyze theinfluence of organizational commitment, leadership, employee performance, andjob satisfaction as intervening variables in PT Madubaru Bantul Yogyakartace.Method of analysis of the data used in this research is descriptive andquantitative. The samples in this study were employees of PT Madubaru amountedto 77 people. Data collection was carried out by using a questionnaire that hasbeen tested for validity and reliability. Data analysis method was using classicassumption test, path analylisis, as well as the coefficient of determination.Descriptive analysis shows that organizational commitment, leadership, jobsatisfaction and employee performance was moderate. Based on the results ofmultiple linear analysis and test of Sobel test indicates that organizationalcommitment, leadership, positive influence on employee performance and jobsatisfaction mediate organizational commitment and leadership on employeeperformance. The coefficient of determination shows that the work satifaction ofPT Madubaru Bantul Yogyakarta are influenced by organizational commitment,leadership and job satisfaction by 32.o%, while the remaining 68,0% areinfluenced by other variables in which the research did not examined in this study.The coefficient of determination shows that the employees performance of PTMadubaru Bantul Yogyakarta are influenced by organizational commitment,leadership and job satisfaction by 47,7%, while the remaining 52,3% areinfluenced by other variables in which the research did not examined in this studyKeywords : organizaitonal commitment, leadership, work satisfaction, andemployees performance